DISOBEDIENCE OF CONFUCIAN RULES IN MAXINE HONG KINGSTON’S THE WOMAN WARRIOR - Happy Simamora (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This study aims to find and analyze the disobedience to Confucian rules that found in Maxine Hong Kingston's The Woman Warrior. This research uses qualitative methods with data collection done through comprehensive reading, marking relevant data, reading the concepts and theories applied and removing irrelevant data and writing the most relevant to be analyze. The data analyze with feminist theories. The results found are that there are Confucian rules that do not support gender equality or demean women. Therefore, through her work Kingston expresses disobedience to these rules. The rules that found are: Match making, the difference between boys and girls, humility, husband's and wife's duties, wholehearted devotion, and silencing women. Through this research, women must dare to get out of their comfort zone, to be independent, speak up, and not be afraid of restrictive rules, and have a freedom to do domestic and public roles.